UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD SISWA KELAS III SDN 001 PENDALIAN IV KOTO - Yuliastuti, Rita; Saragih, Sehatta; ', Sakur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is classroom action research that aims to improve the students mathematics achievement by implementing the cooperative learning type STAD. The subject of this research was the third grade students at class III SDN 01 Pendalian IV Koto in the second semester academic years 2014/2015. There were 20 students which consist of 11 boys and 9 girls who have heterogeneous academic ability. This research was implemented in two cycles, and at the end of every cycle carried out mathematics achievement test. Data collected through observation and mathematics achievement test. The results of this research showed that the activities of teacher and students have done well after doing the action. The students learning process have more focussed on increasing the knowledge and students interaction become better. Most of students were excited and more active in learning process, such as while they were doing the steps of learning, like preresenting students’ worksheet or questions, respond to their friend’s presentation and giving the conclusion of learning. The action was successful if the number of students who got the score of minimum mastery criteria increase in mathematics achievement tests I and II. The number of students who got the base of score of minimum mastery criteria on the first mathematics achievement test I (first cycle) and the second mathematics achievement test II (second cycle) are respectively 25%, 45%, and 60%. The results of this research indicates that the cooperative learning type STAD can improve the mathematics achievement of the third grade students at class III SDN 01 Pendalian IV Koto.Keywords: Mathematics Achievement, Cooperative Learning Type of STAD, Class Action Research